2014
DOI: 10.1097/nmd.0000000000000220
|View full text |Cite
|
Sign up to set email alerts
|

Early Recognition of Obsessive-Compulsive Disorder

Abstract: The early course in clinical and neurobiological terms of obsessive-compulsive disorder (OCD) is almost completely unknown. The disease often begins in early childhood and adolescence, but the first behavioral changes and symptoms preceding OCD have not been assessed to date. In this retrospective approach, 40 patients with OCD (23 females/17 males; 39.4 [10.1] years old in average; with scores on the Yale-Brown Obsessive-Compulsive Scale [Y-BOCS] of 19 [9.3]) were given an author-developed questionnaire. Twen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Most patients showed obsessions and compulsive behaviour, a finding consistent with the results of Matsunaga. 34 The five most frequently reported obsessive and compulsive symptoms were similar to Juckel et al's findings 35 ("enhanced feeling of responsibility," "exact attention concerning details," "difficulties with decisions," and "repetitive controlling"). In the present study, the distribution of obsessive and compulsive symptoms in primary school students was significantly different from that in junior high school and senior high school students.…”
Section: Ethics Approvalmentioning
confidence: 53%
See 1 more Smart Citation
“…Most patients showed obsessions and compulsive behaviour, a finding consistent with the results of Matsunaga. 34 The five most frequently reported obsessive and compulsive symptoms were similar to Juckel et al's findings 35 ("enhanced feeling of responsibility," "exact attention concerning details," "difficulties with decisions," and "repetitive controlling"). In the present study, the distribution of obsessive and compulsive symptoms in primary school students was significantly different from that in junior high school and senior high school students.…”
Section: Ethics Approvalmentioning
confidence: 53%
“…The Y-BOCS severity scale 17 consists of 10 questions scored on a scale of 0 to 4 that assess the severity of obsessions and compulsions. Total severity scores are usually assumed to indicate the following levels of OCD: subclinical (0-7), mild (8)(9)(10)(11)(12)(13)(14)(15), moderate (16)(17)(18)(19)(20)(21)(22)(23), severe (24)(25)(26)(27)(28)(29)(30)(31) and extremely severe (32)(33)(34)(35)(36)(37)(38)(39)(40). A mild level of OCD is generally considered clinically significant, but previous studies have tended to consider scores !16 points as the inclusion criteria for OCD.…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, the subjective feeling of restlessness, part of the akathisia, is close to the distress seen in patients with the urge to control or suppress compulsions in response to intrusive thoughts [ 5 ]. Little is known about the early course of OCD and even less is known concerning the early course of OCD in schizophrenia, but a retrospective study reported that “anxiety” and “lacking self-trust” were frequent first signs of developing OCD [ 18 ]. Specifically, the anxiety could partially overlap with mild akathisia.…”
Section: Discussionmentioning
confidence: 99%
“…Poor recognition of harm and taboo content were identified as reasons for underdiagnosis ( García-Soriano et al, 2014 ). Moreover, the separation of OCD from the chapter of anxiety disorders in the DSM-5 may have decreased detection of these cases, especially in pediatric patients, who present prodromally with anxiety ( Juckel et al, 2014 ; Burchi and Pallanti, 2018 ). This suggests the necessity of improving early detection of cases and sensitivity of assessment.…”
Section: Recovery-oriented Program In Ocd: What We Already Have Whatmentioning
confidence: 99%